2020
DOI: 10.1002/pits.22462
|View full text |Cite
|
Sign up to set email alerts
|

Using structural equation modeling to examine the relationship between Ghanaian teachers' emotional intelligence, job satisfaction, professional identity, and work engagement

Abstract: The purpose of the study was to examine the causal relationship between teachers' emotional intelligence, job satisfaction, professional identity, and work engagement. And to achieve this purpose, a questionnaire consisting of four scales was administered to 260 teachers selected from the Adentan Municipal in the Greater Accra Region. Exploratory factor analysis, structural equation modeling, and univariate statistical analyses were employed to analyze the data. Results of the analyses established that job sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 65 publications
6
30
0
6
Order By: Relevance
“… Van Der Want et al (2019) found a significant relationship between teachers’ professional identity and work engagement. Butakor et al (2021) found that teachers’ professional identity is considered an essential issue in instructors’ engagement with their job, which regulates learners’ educational success. They also argued that emotional intelligence positively influenced teacher professional identity and job satisfaction which affected work engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Van Der Want et al (2019) found a significant relationship between teachers’ professional identity and work engagement. Butakor et al (2021) found that teachers’ professional identity is considered an essential issue in instructors’ engagement with their job, which regulates learners’ educational success. They also argued that emotional intelligence positively influenced teacher professional identity and job satisfaction which affected work engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers’ WE can be regarded as important in terms of overall success of schools because previous research found statistically significant and positive relationships between teacher WE and student achievement ( Wilson and Corcoran, 1988 ; Bakker, 2005 ). Cardwell (2011) also argued that one of the predictors of student engagement is teacher engagement (cited in Butakor et al, 2020 ). Engaged teachers achieve more than their formal responsibilities and duties and support their students academically by following various approaches and methods resulting in better a academic performance ( Kirkpatrick, 2009 ; Ariani, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a discussion in the literature regarding the causal order between JS and WE (Yalabik, Popaitoon, Chowne, & Rayton, 2013). On the one hand, some studies show that highly engaged employees are characterized by being more immersed and dedicated to their work as a consequence of how challenging and inspiring it is, thus triggering higher JS (Karanika-Murray, Duncan, Pontes, & Griffiths, 2015;Lu et al, 2016); and on the other, previous evidence also indicates that WE is an active state that is strongly influenced by employees' JS (Butakor, Guo, & Adebanji, 2021;Vokić & Hernaus, 2015). In this sense, this research suggests JS as a predictor…”
Section: Mediating Role Of Job Satisfactionmentioning
confidence: 99%